1995
DOI: 10.1017/s0950268800058210
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis A antibody among disadvantaged gypsy children in northern Spain

Abstract: The prevalence of antibody to hepatitis A virus (HAV) in a group of socially and economically disadvantaged Spanish gypsy children was compared to that of a group of non-gypsy middle-class children. The study included 438 children, 73 gypsies (38 girls and 35 boys, mean age 8.5 years, age range 2-16 years) and 365 non-gypsy controls, randomly selected by age. The presence of anti-HAV was investigated using ELISA. Among the gypsy children, 82% had antibodies to HAV compared with 9.3% of the children in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
1
4
1
1
Order By: Relevance
“…Recently, young maternal age has been independently associated with a higher risk of bronchiolitis-associated deaths in the United States [15]. Interestingly, 5 % of the infants hospitalized in that study belonged to the gypsy ethnic group, a proportion higher than that in our population, which, lacking official statistics, we estimate is lower than 1 % [16]. This finding is probably related to the lower socio-economic status of these families and presents similarities with the situation found in some minority ethnic groups, among which the incidence rates of hospitalization due to RSV infections or bronchiolitis were higher than those among the general paediatric population [17,18].…”
Section: Discussioncontrasting
confidence: 63%
“…Recently, young maternal age has been independently associated with a higher risk of bronchiolitis-associated deaths in the United States [15]. Interestingly, 5 % of the infants hospitalized in that study belonged to the gypsy ethnic group, a proportion higher than that in our population, which, lacking official statistics, we estimate is lower than 1 % [16]. This finding is probably related to the lower socio-economic status of these families and presents similarities with the situation found in some minority ethnic groups, among which the incidence rates of hospitalization due to RSV infections or bronchiolitis were higher than those among the general paediatric population [17,18].…”
Section: Discussioncontrasting
confidence: 63%
“…The fact that some of Roma population do not have basic provision of sewerage, water supply and waste disposal could explain the high prevalence of HAV. Previous studies on the epidemiology of HAV in Mediterranean Countries have shown the association with socioeconomic, hygienic and housing conditions [Morales et al, 1992;Papaevangelou, 1992;Cilla et al, 1995]. Although in our study we did not include many members from the same families, there was some indication for intrafamilial transmission of the virus at least among siblings attending elementary schools, a finding that has also been previously reported by other investigators [Roumeliotou et al, 1992].…”
Section: Hepatitis Asupporting
confidence: 74%
“…Seroprevalence surveys in pregnancy26 27 show high levels of infection with hepatitis A and B (which can be transmitted vertically). A study in Spain34 found a seroprevalence of HAV antibodies of 82% in deprived Roma children compared with 9.3% of more affluent non-Roma children. In another Spanish study,35 three groups were compared; non-Roma children, Roma children, and children in orphanages.…”
Section: Resultsmentioning
confidence: 99%